The Role of Religiosity and Social Support in Predicting Gratitude Among Adolescents and Adults - Al-Asmari, Abdullah Abdulrahman; Hakami, Ibrahim bin Qasem; Al-Zahrany, Bandar Alalam (Journal of Ecohumanism, 2025)
This study investigates the predictive role of religiosity and social support in fostering gratitude. It further aims to elucidate the intricate relationships between gratitude, religiosity, and social support. Additionally, the study seeks to identify potential age-related differences in gratitude between adolescents and adults. The study employed a convenience sample of 175 participants from the Kingdom of Saudi Arabia, specifically Riyadh. The sample comprised two age groups: adolescents (n = 95) and adults (n = 80). The adolescent group consisted of high school students (boys and girls) with an average age of 15.8 years (SD = 0.54). The adult group included teachers from the same schools with an average age of 29 years (SD = 5). participated in this study. Data collection employed validated instruments: the Arabic Multidimensional Social Support Scale (MDSSS) by Dion & Dunn et al. (1987) adapted by Aserssa & Abdel-Maksoud (2001), the Arabic Gratitude Questionnaire (GQ-6) by McCullough & Emmons (2002) further refined by Southpaw et al. (2005), and a researcher-developed measure of religiosity. Analysis revealed significant positive relationships between religiosity and social support, with adults exhibiting higher gratitude than adolescents. Importantly, all three variables (religiosity, social support, and peer support) emerged as significant predictors of gratitude.